A rapid questionnaire assessment of environmental exposures to pregnant women in the INTERGROWTH‐21st Project. (9th September 2013) - Eskenazi, B; Bradman, A; Finkton, D; Purwar, M; Noble, JA; Pang, R; Burnham, O; Cheikh Ismail, L; Farhi, F; Barros, FC; Lambert, A; Papageorghiou, AT; et al.
Abstract : Impaired fetal growth and preterm birth are the leading causes of neonatal and infant mortality worldwide and there is a growing scientific literature suggesting that environmental exposures during pregnancy may play a causal role in these outcomes. Our purpose was to assess the environmental exposure of the Fetal Growth Longitudinal Study (FGLS) participants in the multinational INTERGROWTH‐21 st Project. First, we developed a tool that could be used internationally to screen pregnant women for such exposures and administered it in eight countries on a subsample ( n = 987) of the FGLS participants. The FGLS is a study of fetal growth among healthy pregnant women living in relatively affluent areas, at low risk of adverse pregnancy outcomes and environmental exposures. We confirmed that most women were not exposed to major environmental hazards that could affect pregnancy outcomes according to the protocol's entry criteria. However, the instrument was able to identify some women that reported various environmental concerns in their homes such as peeling paint, high residential density (>1 person per room), presence of rodents or cockroaches (hence the use of pesticides), noise pollution and safety concerns. This screening tool was therefore useful for the purposes of the project and can be used to ascertain environmental exposures in studies in which the primary aim is not focused on environmental exposures. The instrument can be used to identify subpopulations for more in‐depth assessment, (e.g. environmental and biological laboratory markers) to pinpoint areas requiring education, intervention or policy change.